Evaluation of the Association between Medication Use and Sleep Quality among Shift Workers versus Day Workers - Rosado, Magda Margarida Granadeiro; Carvalho, Lucinda Sofia; Coelho, André (Sleep Science, 2024)
Objective Different factors, such as medication use and shift work, can influence sleep quality. We aimed to determine the association between medication use and sleep quality in shift workers versus daytime workers.Materials and Methods We conducted a quantitative cross-sectional study with a convenience sample of active workers. Online questionnaires were applied to assess sleep quality, sleepiness, medication use, and sociodemographic characteristics.Results A total of 296 participants were included: 124 (41.89%) daytime workers and 172 (58.11%) shift workers. In total, 130 (43.92%) participants worked in the healthcare sector, 116 (39.19%), in industry, and 50 (16.89%), in other sectors. After a bivariate analysis, poor sleep quality was associated with the presence of sleep disorders (p < 0.001), type of work (shift or day work) (p < 0.001), and the use of sleeping medication (p < 0.001). Although shift workers had worse sleep quality, no differences were found regarding the use of medications that act directly on the central nervous system or with proven effects on sleep. No association was found between medication use and sleep quality. When adjusted for the different variables that were individually associated with poor sleep quality, through a logistic regression model, none showed an increased risk of poor sleep quality.Discussion In spite of the need for further research, our results have shown that sleep quality is influenced by many different factors whose impact must be evaluated in combination, and not just in a bivariate manner. There are many factors individually associated with poor sleep quality, but when adjusted to each other, they have shown no increased risk of having poor sleep quality.
Keywords: sleep quality; sleep disorders; shift work; medication use